CHRONOTOPIC STRUCTURES AND THEIR INTERACTION IN J. R. R. TOLKIEN’S THE LORD OF THE RINGS (Eureka Journal of Language, Culture & Social Change, 2026)
The article examines the system of chronotopes in J. R. R. Tolkien’s The Lord of the Rings and the principles governing their interaction. It argues that the artistic world of the novel is constructed at the intersection of mythopoetic, epic, adventure, and idyllic models of space-time organization. Particular attention is paid to the chronotopes of the road, feast, battle, and Otherworld, as well as to their role in shaping the semantic structure of the narrative. The symbolism of the One Ring, the White Tree, the Shire, Lothlórien, and the Grey Havens is analyzed. The article concludes that the chronotopic system of the novel unites the hero’s private destiny with the historical and mythological fate of the world, bringing together the local and the universal, the domestic and the sacred, the earthly and the transcendent.
Keywords: Chronotope, J.R.R. Tolkien, The Lord of the Rings, mythopoetics, epic, road, Otherworld, Lothlórien, Shire, White Tree.